Ancient Manuscripts in Digital Culture Visualisation, Data Mining, Communication (Volume 3) - Hamidović, David; Clivaz, Claire; Bowen Savant, Sarah (Brill, 2019)
Ancient Manuscripts in Digital Culture presents an overview of the digital turn in Ancient Jewish and Christian manuscripts visualisation, data mining and communication. Edited by David Hamidović, Claire Clivaz and Sarah Bowen Savant, it gathers together the contributions of seventeen scholars involved in Biblical, Early Jewish and Christian studies. The volume attests to the spreading of digital humanities in these fields and presents fundamental analysis of the rise of visual culture as well as specific test-cases concerning ancient manuscripts. Sophisticated visualisation tools, stylometric analysis, teaching and visual data, epigraphy and visualisation belong notably to the varied overview presented in the volume.